Examining the Legitimacy of the Myanmar Military Coup in the Eye of International Law: After the 2020 Elections - Haikal Wicaksono; Khoirur Rizal Lutfi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The forced takeover of a country's government is also known as a coup (Coup d’état), the coup has become a polemic on its legitimacy in international law, such as the coup incident in Myanmar after the 2020 elections carried out by the highest military power holder or the head of the Myanmar military junta. The regulation regarding the coup d’état in the eyes of international law must be studied properly and correctly. The existence of the Montevideo Convention on the Rights and Duties of the State equips international countries so that coups are not carried out arbitrarily, resulting in violations of the rules of international law. Looking at the Myanmar military coup from the concept of international recognition of the government of a country, then from the concept of international recognition of the succession of the Myanmar government. Then how is the concept of international recognition of the government that can be obtained or comes from the coup d'etat. And about how the legitimacy of the coup as a form of transition of government in the perspective of International Law. So that it becomes clear about the Myanmar military coup action which is right if it does not violate the rules of international law and becomes wrong if it violates the rules of international law.